Radiology in Emergency Medicine: Diagnostic Imaging for Acute Stroke Management - Maha Muthqal Alshammari; Eman Gadban Alkhomashi; Majedah Fehan Alshammari; Ahmed Mohammed Asiri; Rana Saleh Alghaithi; ‏Faris Abdrhman Alshammari; Abdulsalam Abdulaziz Almulayfi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Acute stroke is a major global health issue responsible for many of the deaths; therefore the early diagnosis and treatment of acute strokes is a crucial part of this branch of medicine. Diagnostic imaging is an inseparable component of diagnosis of stroke, helping clinician to define the nature, location, and the degree of the event. Currently the use of diagnostic imaging in acute stroke has significantly improved and allows for the rapid and accurate separation of ischemic and hemorrhagic stroke which is critical to early management. Aim of work: To explore the critical role of radiology in the emergency management of acute stroke, highlighting the various diagnostic imaging modalities used, their applications, and their impact on therapeutic decision-making. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Radiology, Emergency Medicine, Diagnostic Imaging, Acute Stroke, and Management. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Imaging in particular is a key modality in the emergency management of acute stroke as it is the basis upon which initial and subsequent treatment is both planned and carried out. Whether to distinguish ischemic stroke from hemorrhagic stroke or make therapeutic decisions or determine the prognosis, NCCT, CTA, CTP and MRI are invaluable tools. With even the current generation of imaging technology being potent, let alone the use of AI and new techniques expected to improve the accuracy and availability of stroke treatment. However, to build on the successes of SWIFT and similar studies, and to enhance the capacity to reduce the global burden of future stroke, future challenges will need to be addressed effectively, including the problem of limited resources and factors that influence heterogeneity in implemented imaging strategies.